The Potential of Bacillus spp. in Suppressing Colletotrichum capsici that Causes Antracnose in Red Chili - Rani, Sasiska; Endang Triwahyu Prasetyawati; Herry Nirwanto; Sri Wiyatiningsih (International Journal of Applied Biology, 2023)
Red Chili (Capsicum annum L.) is a horticultural plants that is classified as an important commodity and has high economic value. One of the main problems in the production of red chili is anthracnose disease caused by the Colletotrichum capsici pathogen. Bacillus spp. expected to have the potential to inhibit the growth of C. capsici and stimulate the growth of plant. This study aims to determine the potential of Bacillus spp., in suppressing the growth of the C. capsici fungus and stimulating the growth of red chili. This study used a Completely Randomized Design (CRD) with the treatment without Bacillus spp., chemical fungicides, Bacillus sp. (Ba-6), Bacillus sp. (Ba-9), Bacillus sp. (Ba-12), Bacillus sp. (Ba-15), and Bacillus sp. (Ba-17). The treatment was repeated 4 times and the treatment unit contained 5 red chili/polybag. The results showed that the highest suppression of C. capsici in the treatment of Bacillus sp. Ba-15 was 6.25% compared to the negative control. The best bacteria that can stimulate the growth of red chili is Bacillus sp. Ba-9 with an average plant height 20.10 cm and an average number of leaves 10.49